A novel method for vascular age estimation via pressure pulse wave of radial artery. (September 2022) - Tang, Qingfeng; Tao, Changlong; Pan, Zhiqiang; Wang, Guangjun; Liu, Kui; Pan, Zhigeng; Liu, Guodong; Su, Benyue; Liu, Ning
Highlights: To our knowledge, this is the first study to estimate vascular age with pressure pulse wave of radial artery. This study proposes a new method to assess the effect of lifestyle on vascular aging. The vascular age obtained by our method is a more effective direct index to evaluate vascular aging than chronological age. Abstract: Chronological age (CA) has been identified to be an important independent risk factor for cardiovascular disease. However, there are still some limitations for CA in evaluating the actual vascular aging due to the effect of lifestyles (EL). This study aexplores a new index vascular age (VA) to replace CA. Given that VA mainly depends on CA and EL, how to determine EL (AgeEL ) becomes the key issue in this study. Firstly, we extract ten shape features called relative equal pressure pulse transit time (R-PTT) from the pulse signal as independent variables, and take CA as dependent variable to establish multiple linear regression (MLR) model. Secondly, we input these R-PTTs into the MLR model to calculate the predicted age (PAr ) of each subject, and then adopt PAr as the reference for individual vascular aging. Thirdly, the expectation of the predicted ages (PAe ) in each CA group is calculated to evaluate the collective vascular aging of the CA group. Finally, we obtain AgeEL according to PAr and PAe, and then estimate the value of VA. Overall, the VA achieved in this research is closer to six objective indirect indices describing vascular aging than CA, such as augmentation index (AIx), pulse transit time (PTT), diastolic augmentation index (DAI), etc. The VA obtained in this study is more effective in evaluating vascular aging than CA, which may be useful in screening premature vascular aging for young people in the field of public health.